Rural-Urban Migration among Secondary School Graduates in the Southern Senatorial Zone of Kaduna State: Causes and Effects on Agricultural Production - M., Alkali; S. M., Danjuma (Journal of Home Economics Research, 2024)
The study sought to determine the causes of Rural-Urban migration among secondary school graduates in the Southern Senatorial Zone of Kaduna State and how it affects agricultural production. Two research questions and two hypotheses guided the study. The population for the study was 264 comprising of 41 Agricultural Development Project (ADP) Extension Agents and 223 teachers of agriculture in the three educational inspectorate divisions in the area of study. The sample used for the study was 131 respondents. Questionnaire was used for data collection. Data was analyzed using the mean to answer the research questions while the t-test statistic was employed in testing the hypotheses of the study. Major findings include that lack of good road network, poor prices of agricultural products among others are causes of rural-urban migration. Respondents also perceived low agricultural production, poverty, hunger, food insecurity, loss of the most informed and enterprising portion of the rural population among others as effects of rural urban migration on agricultural production. The results of the test of hypotheses showed that there was no statistical significant difference in the Mean Responses of the respondents. It was recommended that government and non-governmental organizations should come up with policies and programs that will lead to the development of the rural areas such as rural roads construction, rural electrification, farm input subsidy, rural health services among others.